3D computer‐aided treatment planning in periodontology: A novel approach for evaluation and visualization of soft tissue thickness. Issue 5 (25th June 2020) - Kuralt, Marko; Gašperšič, Rok; Fidler, Aleš
Abstract: Objective: Current approaches for soft tissue thickness evaluation and visualization still represent a challenge for full extent evaluation and visualization. The aim of this clinical technique article is to introduce a novel approach for comprehensive visualization and precise evaluation of oral soft tissue thickness utilizing a fusion of optical 3D and cone‐beam computed tomography (CBCT) images. Clinical considerations: 3D models of the maxilla were obtained by CBCT imaging and intraoral scanning. The CBCT images were reconstructed to standard tessellation language (STL) file format models by segmentation of teeth and bone using implants planning software. 3D soft tissues and teeth models were obtained by intraoral scanning and were exported in STL file format as well. 3D multimodal models were then superimposed using best‐fit matching on teeth. Soft tissue thickness was then visualized and evaluated with a 3D color‐coded thickness map of gingival and palatal areas created by surface comparison of both 3D models. Additionally, threshold color‐coding was used to increase comprehensibility. Palatal areas were further visualized and evaluated for the optimal donor site. Conclusions: A novel approach for 3D evaluation and visualization of masticatory mucosa thickness presents all available 3D data in a comprehensible, "clinician‐friendly" manner, using threshold regions and clinically relevant views. Clinical significance: Proposed approach could provide comprehensive presurgical treatment planning in periodontal plastic surgery and implantology without additional invasive procedures for the patient, resulting in more predictable treatment, improved outcomes, and reduced risk for complications.